Effects of patient education on desire for twins and use of elective single embryo transfer procedures during ART treatment: A systematic review. (August 2018) - Sunderam, Saswati; Boulet, Sheree L.; Jamieson, Denise J.; Kissin, Dmitry M.
Abstract: Twin births among users of assisted reproductive technology (ART) pose serious risks to both mothers and infants. However, patients may prefer twins and may be unaware of the risks of twin pregnancies. Increasing use of elective single embryo transfers (eSET) through improved patient education could help to reduce twin births and related adverse health consequences. A systematic review of PUBMED and EMBASE databases was conducted to evaluate the effectiveness of patient education among ART users on knowledge of twin pregnancy risks, desire for twins, preference for or use of eSET, and twin pregnancy rates. Of 187 references retrieved, six met the selection criteria. Most focused on patients undergoing their first ART cycle aged < 35 years. Patient education was delivered via written materials, DVDs or discussion. Four studies reporting on knowledge of risks or desire for twins showed significant effects of oral and written descriptions of multiple pregnancy complications, risks of twins versus singletons, and DVDs with factual information. Five studies showed increased eSET use or preference after patients were educated on the risks of multiple pregnancy and success rates associated with different types of ART procedures, when combined with clinic policies that supported single blastocyst transfers or provided options for insurance. In younger ART users, patient education on twin pregnancy risks and success rates of eSET may improve knowledge of twin pregnancy risks and increase use of eSET, and may be important for wider implementation of eSET in countries such as the USA where the use of eSET remains low. Clinic policies of single blastocyst transfers or financial incentives may strengthen these effects.